Many Faces of Thoracic Histoplasmosis—Pictorial Essay. Issue 3 (August 2019) - Semionov, Alexandre; Rossi, Anthony; Perillo, Michele; Sayegh, Karl; Pressacco, Josephine; Kosiuk, John
Histoplasmosis is primarily a pulmonary fungal infection with a vast array of radiological manifestations, which can mimic a number of thoracic diseases. This article reviews various presentations of histoplasmosis on chest imaging.